PERANCANGAN USER INTERFACE (UI) PERPUSTAKAAN ONLINE BERBASIS ANDROID - Fastabiq Furoqonul , Pratama; Feby Revita , Rahma; Salman, Abdurahman; Yulia , Dewi; Yulianto, Yulianto; Miftahul , Huda (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2023)
Online libraries have become an important source of information in modern life. To facilitate access and use of libraries, designing a good and intuitive User Interface (UI) is essential. This research aims to design an Android-based online library UI using the prototype method. The prototype method is a design approach that focuses on iterative development of the initial design. This research adopts this method to produce an online library UI that can meet the needs of users effectively. The design process involves steps such as user needs analysis, initial design, prototype implementation, evaluation, and continuous improvement. At the user needs analysis stage, data is collected through surveys and interviews with potential users of the online library. The results of this analysis are used as the basis for the initial design of the UI. Based on the results of the analysis, important features such as book search, loan list, book recommendation, and book category are prioritized in UI design. Once the initial design is complete, the UI prototype is built using Android-based UI design tools. The prototype is then evaluated through testing sessions with potential users. User feedback is obtained and used to make improvements and improvements to the UI. This iteration is done to achieve better UI design and meet user needs. The final result of this research is in the form of an Android-based online library UI design that uses the prototype method. The final design has a display or user interface that suits the user's desire and is easy to use, so that users feel easy in searching for books, viewing loan lists, and finding book recommendations that suit their interests. The prototype method plays an important role in producing UI designs that are responsive to user needs.